2020
DOI: 10.1021/acs.cgd.0c00728
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Polymorphic Behavior of Curcumin during Antisolvent Crystallization: Insights from Raman Spectroscopy and Molecular Modeling

Abstract: The focus of this work is to understand the polymorphic behavior of curcumin crystallized from two different organic solvents by liquid antisolvent (LAS) precipitation carried out in a semibatch mode. LAS precipitation of curcumin from ethanol yielded the metastable (orthorhombic) Form 3, while acetonitrile led to the precipitation of stable (monoclinic) Form 1. These polymorphic crystal structures mirrored clustering of curcumin molecules in the respective organic solutions determined using in situ Raman spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Simultaneous use of these two methods was also applied successfully by other researchers in pharmaceutical and biochemical fields. They were utilized inter alia to study the crystal structure of the chiral antiparasitic drug Praziquantel [ 74 ], examine the equilibrium geometry, bonding features, and harmonic vibrational frequencies in benzothiazole [ 75 ], investigate the polymorphic behavior of crystallized curcumin [ 76 ], explore the interaction of hypericin with serum albumins [ 77 ], and chromate with 4-(2-mercaptoethyl)pyridinium [ 78 ]. In the future, it will be possible to apply these techniques to analyze more types of active compounds in pharmaceutical formulations and guest–host complexes, leading to the design of drugs with appropriate pharmacokinetic properties, thereby increasing their bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous use of these two methods was also applied successfully by other researchers in pharmaceutical and biochemical fields. They were utilized inter alia to study the crystal structure of the chiral antiparasitic drug Praziquantel [ 74 ], examine the equilibrium geometry, bonding features, and harmonic vibrational frequencies in benzothiazole [ 75 ], investigate the polymorphic behavior of crystallized curcumin [ 76 ], explore the interaction of hypericin with serum albumins [ 77 ], and chromate with 4-(2-mercaptoethyl)pyridinium [ 78 ]. In the future, it will be possible to apply these techniques to analyze more types of active compounds in pharmaceutical formulations and guest–host complexes, leading to the design of drugs with appropriate pharmacokinetic properties, thereby increasing their bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…1 d). The peaks centered at 1579 cm −1 could be assigned to ν (C=C) aromatic coupled with pyrrole ring stretching vibration or indole ring vibration from PDA coating [ 55 ] or Cur [ 56 ], and the peak at 1355 cm −1 was due to the aromatic ν(C-N) stretching mixed with indole ring stretching from the PDA coating. These results partly represent the structural features of the monomers composing PDA [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…This shift was particularly notable in the case of alcohols, decreasing in the order MeOH > EtOH > IPrOH > BuOH, in agreement with the decreasing order of solubility data. In the literature, a longer shift to higher wavelengths has been related to a higher propensity of hydrogen bond between the solute and solvent molecules, eventually leading to a higher solubility. In the present study, such a rule clearly applies with the order of solubility found in alcoholic solvents, EA and ACN.…”
Section: Results and Discussionmentioning
confidence: 99%